Temporal dynamics of soil microbial symbioses in the root zone of wolfberry: deciphering the effects of biotic and abiotic factors on bacterial and fungal ecological networks - He, Mengyuan; Wang, Qianqian; Wang, Yiming; Zhang, Junhua (Frontiers in Plant Science, 2025)
Long-term monoculture of Lycium barbarum significantly affects its productivity and soil health. Soil microbiota, which mediate the sustainable development of soil ecosystems, are influenced by the age of wolfberry plants. However, the comprehensive effects of long-term cultivation of L. barbarum on the soil microbial community are not yet fully understood. Here, we assessed the effects of stand age on the diversity, composition, assembly, and symbiotic networks of bacterial and fungal communities in the root zone soil of L. barbarum using high-throughput sequencing technology. The results showed that stand age significantly affected the α-diversity of bacterial and fungal communities, as evidenced by the tendency of their Shannon and Chao1 indices to increase and then decrease. At the same time, the structure of soil bacterial and fungal communities was significantly influenced by tree age. However, Proteobacteria (28.77%–32.81%) was always the most dominant bacterial phylum, and Ascomycetes (49.72%–55.82%) was always the most dominant fungal phylum. A number of genus-level biomarkers were also identified in soils associated with roots of trees of varying ages. Additionally, stochastic processes dominated the assembly of soil bacterial communities, whereas the balance between stochastic and deterministic processes in the assembly of fungal communities fluctuated with stand age. The complexity and stability of bacterial and fungal community networks were notably affected by tree age, particularly in networks from 10- and 15-year-old trees. The partial least squares path modeling (PLS-PM) analysis emphasized that stand age can indirectly regulate the diversity and network complexity of both bacterial and fungal communities by influencing soil physicochemical properties. Furthermore, the bacterial community, but not the fungal community, exhibited direct and strong regulation of network complexity. The study offers valuable data for improving the soil quality and fruit yield of L. barbarum under long-term continuous cropping, which has implications for the sustainable development of the L. barbarum industry.